2021
DOI: 10.1111/are.15273
|View full text |Cite
|
Sign up to set email alerts
|

Molecular confirmation of metacercaria of Clinostomum complanatum recovered from one‐stripe spiny eel Macrognathus aral

Abstract: The one‐stripe spiny eel (Macrognathus aral, Bloch & Schneider, 1801) under the family Mastacembelidae, a native ornamental fish, were collected from the freshwater ponds and canals of West Bengal, with a purpose to raise the colony as ornamental fish broodstock. During acclimatization, fish were found to be lethargic and reluctant to consume feed followed by the appearance of deep wounds and red patches on the ventral part of the body surface. There was a mortality of 40.49% of affected fish within the next 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…Hence, prevalence of parasite in the body cavity were found 51.5%, 33.3%, and 27.0% in C. gariepinus from Lake Haramaya, Lake Tinike, and Lake Adele, respectively, and 17.3% and 12.9% in O. niloticus in Lake Haramaya and Lake Tinike, respectively. However, the result of total overall prevalence of parasite in the body cavity was 29.7%, which is higher than the previous reports of Muluken [59], Bekele and Hussien [63], and McAllister and Robison [81], but lower than Abdullah et al [18], Mahdy et al [24], Salem et al [31], Tesfaye et al [37], Mahdy et al [52], Lima et al [56], Marshet [58], Corrêa et al [76], and Bera et al [80]. The overall prevalence of parasite in the muscle of fish were 32.4%, 19.6%, and 16.4% in C. gariepinus from Lake Haramaya, Lake Tinike, and Lake Adele, respectively, and 16.0% and 8.1% in O. niloticus from Lake Haramaya and Lake Tinike, respectively.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Hence, prevalence of parasite in the body cavity were found 51.5%, 33.3%, and 27.0% in C. gariepinus from Lake Haramaya, Lake Tinike, and Lake Adele, respectively, and 17.3% and 12.9% in O. niloticus in Lake Haramaya and Lake Tinike, respectively. However, the result of total overall prevalence of parasite in the body cavity was 29.7%, which is higher than the previous reports of Muluken [59], Bekele and Hussien [63], and McAllister and Robison [81], but lower than Abdullah et al [18], Mahdy et al [24], Salem et al [31], Tesfaye et al [37], Mahdy et al [52], Lima et al [56], Marshet [58], Corrêa et al [76], and Bera et al [80]. The overall prevalence of parasite in the muscle of fish were 32.4%, 19.6%, and 16.4% in C. gariepinus from Lake Haramaya, Lake Tinike, and Lake Adele, respectively, and 16.0% and 8.1% in O. niloticus from Lake Haramaya and Lake Tinike, respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…The results of the present study showed that the average number of larvae of Contracaecum parasite is similar to that of reported by Tesfaye et al [37] but higher than reported by Abdullah et al [18], Mitiku [35], and Lima et al [56] and lower than Corrêa et al's [76] report. Also, the average of five EMC of Clinostomum was recorded from Clinostomum infected fish, which is lower than reported by Bera et al [80], McAllister and Robison [81], and Aghlmandi et al [82], but higher than reported by Mitiku [35] and Mahdy et al [24]. Therefore, detection of FBZP in the fish from Haramaya District lakes indicates potential public health risk associated with consumption of fish meat from these lakes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The fish were confined in an intensive aquaculture environment in the present investigation. The snails noticed inside the pond could be another source of infection (Bera et al, 2021). The co-habituating cercariae of the snail may be able to identify the second intermediate host in the aquaculture system.…”
Section: Discussionmentioning
confidence: 99%